Role Of Organizational Citizenship Behavior As A Mediateer Of The Influence Of Competency And Work Satisfaction On The Duties Of Health Personnel In The Hospital Covid-19 Statute In The City Of Bengkulu - Gatra Dwi Putra; Fahrudin Js Pareke; Praningrum Praningrum (UNIB Press, 2023)
Researchers are interested in researching the performance of health workers in the new normal era of the Covid-19 pandemic in terms of competence and job satisfaction. Research also examines the role of OCB as an intervening variable, where in previous studies, OCB was placed in the position of the dependent variable. The data used in this study is primary data obtained from the results of distributing questionnaires to respondents using offline dissemination techniques which were distributed to the Covid-19 task force personnel in Bengkulu City consisting of doctors and non-doctors. The sample used in the analysis was 345 people taken by cluster sampling technique. The data analysis method used is descriptive analysis and SEM-PLS analysis. The results of the study show that: (1) Competence significantly influences the OCB of the Covid-19 task force health workers in Bengkulu City; (2) Job satisfaction has a significant effect on the OCB of the Covid-19 task force health workers in Bengkulu City; (3) OCB has a significant effect on the task performance of the Covid-19 task force health workers in Bengkulu City; (4) OCB mediates the effect of competence on the task performance of the Covid-19 task force health workers in Bengkulu City; and (5) OCB mediates the effect of job satisfaction on the task performance of health workers in the Covid-19 task force in Bengkulu City. Keywords: Competence, Work satisfaction, OCB and Task performance